Chitosan Nanofibrous Dressing Increased Angiogenesis and Anti-inflammatory Response in an Acute Wound Model in Rats: A Comparative Study - Yury Salkovskiy; Mahboubeh Ghanbari; Carlos P. Jara; Sara Cartwright; Pinaki Mondal; Colman Freel; Sayed Ahmadreza Razian; Jason MacTaggart; Mark A. Carlson (Annals of Biomedical Engineering, 2025)
Purpose Chitosan-based materials are promising for wound healing because of their antibacterial efficacy, biocompatibility, and biodegradability, though their healing mechanisms remain unclear. This study explores the cellular and molecular mechanisms of wound healing with chitosan nanofibrous dressings. Methods Thirty-nine Sprague Dawley rats were divided into three groups based on the type of dressings administered: (1) chitosan nanofibrous dressing + transparent film, (2) commercial scaffold + transparent film, and (3) transparent film alone (control). Full-thickness wounds (2 cm × 2 cm) were created on the dorsum, splinted, and covered with dressings. Evaluations at 7, 14, and 21 days included histological analysis, and measurements of TNF-α and iNOS levels in the wounds. Results On day 21, epithelialization was significantly higher in the chitosan group than in the scaffold group (87.5% vs. 42.0%, p = 0.03). TNF-α levels were lower in both treatment groups compared to the controls. In the chitosan group, the CD68+/CD163+ ratio was lower than in the scaffold group (0.28 vs. 0.62, p = 0.037), and blood vessel formation was greater than in the controls. Conclusion These results suggest that chitosan nanofibrous dressings enhance acute wound healing in rats by promoting re-epithelialization, neovasculogenesis, and maintaining low TNF-α levels in the later phases of healing.